2001
DOI: 10.1089/105072501750159697
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Some Different Methods for Analysis of Thyroid Autoantibodies: Importance of Thyroglobulin Autoantibodies

Abstract: Blood samples from 141 children and adolescents were used to evaluate differences between commercial kits and radioimmunoassay (RIA) methods for detecting thyroid autoantibodies. Thyroglobulin autoantibodies (Tg-Ab) were analyzed with a hemagglutination kit and a RIA; thyroid peroxidase autoantibodies (TPO-Ab) were measured with a gelagglutination assay and a RIA. The results of the antibody tests were compared with thyroid function tests (triiodothyronine [T3], thyroxine [T4], thyrotropin [TSH]) and with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Actually, to our knowledge, no similar data are present in literature: in the past, other studies faced the same topic but with small numbers of different analytical methods, most of which are no longer in use [9, 15–22, 29]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, to our knowledge, no similar data are present in literature: in the past, other studies faced the same topic but with small numbers of different analytical methods, most of which are no longer in use [9, 15–22, 29]. …”
Section: Discussionmentioning
confidence: 99%
“…Analytical limitations of serum TgAb assays have been reported in the context of thyroid autoimmunity diagnosis [9]. Despite standardization against the International Reference Preparation (IRP) MRC 65/93, several studies demonstrated a high variability in the analytical performances of different TgAb IMAs: large variation in limits of detection (LOD), FS, inter-method results, reference intervals with poor concordance between TgAb assays in patients with DTC [15–22]. The difficulty in standardization is in part due to the heterogeneous Tg immunoreactivity: differential splicing of Tg mRNA, various post-translational modifications, and alterations of biosynthesis regulation in thyroid tumor cells lead to exposure or masking of epitopes with resulting differences in Tg immunologic structure [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrations of anti-TPO and anti-Tg in human serum of ATD patients are in range from 0.05 to 1.4 g/L (Beever et al, 1989) and do not exceed 10% of the concentration of total IgG. Probe "ATD" containing 1200 IU/mL anti-TPO plus 1500 IU/mL anti-Tg was used as single source of both autoantibodies, since just a few of HT patients have serum anti-TPO without anti-Tg (Lindberg et al, 2001). Probe "healthy" containing 25 IU/mL anti-TPO plus 52 IU/mL anti-Tg was used as a negative control, though it has slightly low concentrations of anti-TPO and anti-Tg, so called "natural autoantibodies", which commonly present in serum of healthy donors (Lleo et al, 2010).…”
Section: Elisa Testing Of Cff-sc To Validate Selection Of the Fractiomentioning
confidence: 99%
“…A simplification of the AITD diagnostic process using only the TPOAb assay, which is considered the most sensitive test, especially for Hashimoto's thyroiditis (HT), was recently proposed (3,4). However, this simplification is not universally accepted, because recent studies have reassessed the diagnostic role of TgAb, which has proved to be present alone in high concentrations in a fairly large percentage of patients suffering from HT (9)(10)(11), and seems to be evoked by specific epitopes present in the Tg molecule (12,13). However, this simplification is not universally accepted, because recent studies have reassessed the diagnostic role of TgAb, which has proved to be present alone in high concentrations in a fairly large percentage of patients suffering from HT (9)(10)(11), and seems to be evoked by specific epitopes present in the Tg molecule (12,13).…”
Section: Introductionmentioning
confidence: 99%